The wicked remain ebook - Pohl, Laura (The Grimrose Girls, 2022)
At Grimrose Académie, the fairy-tale deaths continue. And unless the curse is broken, one of the girls could be next. Nani, Yuki, Ella, and Rory have discovered the truth about the curse that's left a trail of dead bodies at Grimrose. But the four still know nothing of its origins, or how to stop the cycle of doomed fates. And each girl harbors her own secret. One is learning why she was brought to the school. One struggles to keep her new and deadly power under control. One knows exactly how much time she has left. And one, trying to escape her dark destiny, will come even closer to fulfilling it. Can the girls change their own stories and break the curse? Or must one of them die to end it forever? Perfect for fans of: Cinderella is Dead and GRIMM Dark Academia Fairytale Retellings LGBTQ Rep Media Buzz for The Grimrose Girls: Buzzfeed called it "a book definitely worth picking up" One of Book Riot 's Top New YA Paperbacks for Fall A Buzzfeed Top LGBTQ+ YA Book to Devour A Culturess Thrilling New YA Release Featured on Tor as a new Young Adult SFF A Barnes & Noble OUR MONTHLY PICK for November 2021!! Praise for New York Times Bestseller The Grimrose Girls: "Enthralling... Fans of empowering feminist fairy-tale retellings will love this." —Kirkus Reviews, STARRED REVIEW "Darkly haunting and achingly romantic." —Ashley Poston, national bestselling author of Geekerella  "Sink your teeth into this story and let it carry you through the woods." —Roseanne A. Brown, New York Times bestselling author of A Song of Wraiths and Ruin